Th1-Like Treg Cells Are Increased But Deficient in Function in Rheumatoid Arthritis - Zhang, Rui; Miao, Jinlin; Zhang, Kui; Zhang, Bei; Luo, Xing; Sun, Haoyang; Zheng, Zhaohui; Zhu, Ping (Frontiers in Immunology, 2022)
Objectives: The present study aimed to investigate the changes in quantity and function of T helper (Th)-like T regulatory (Treg) cell subsets in peripheral blood (PB) and synovial fluid (SF) from rheumatoid arthritis (RA) patients, as well as to understand their relationship with disease activity. Methods: A total of 86 RA patients and 76 gender and age matched healthy controls (HC) were enrolled in this study. Th-like Treg frequency and function were determined using flow cytometry. The inhibitory function of Th-like Treg cells was detected using an in vitro co-culture suppression assay. Results: The proportion and absolute number of Th1-like Treg cells from RA PB and RA SF were significantly higher than those of HC PB. In RA SF, the proportions of Treg cells and Th1-like Treg cells were significantly lower in the elevated erythrocyte sedimentation rate or the C-Reactive Protein group, as well as in the positive groups of anti-CCP antibody and anti-MCV antibody. In addition, the proportions of Treg cells and Th1-like Treg cells from RA SF were negatively correlated with disease activity. However, the expression levels of CD73 and TGF-β1 in Th1-like Treg cells were decreased and these Treg cells could not effectively inhibit the proliferation of effector T (Teff) cells. Conclusion: Our data indicate that Th1-like Treg cells are the predominant Treg cell subset in RA SF, but their suppressive function is defective. Improving the function of Th1-like Treg cells may control the inflammation in joints and provide new strategies for Treg-targeted therapies in RA.